Environmental, Social, and Governance Disclosure and Financial Performance: Evidence from Indonesian Mining Companies - Kania Marsya Pramitha; Arwan Gunawan (FEBI IAIN Langsa, 2026)
Environmental, Social, and Governance (ESG) disclosure has become an important instrument for promoting corporate sustainability and improving financial performance. However, previous studies have reported inconsistent findings regarding the relationship between ESG disclosure and financial performance, particularly in Indonesian mining companies. Moreover, empirical evidence examining the individual effects of environmental, social, and governance disclosures while controlling for firm size remains limited. This study aims to analyze the influence of Environmental, Social, and Governance (ESG) disclosure on the financial performance of mining companies listed on the Indonesia Stock Exchange during 2019–2024. A quantitative explanatory approach was employed using balanced panel data from 14 mining companies, resulting in 84 firm-year observations selected through purposive sampling. ESG disclosure was measured using the Global Reporting Initiative (GRI Standards 2021) disclosure index, in which disclosed indicators were scored one and undisclosed indicators were scored zero. Financial performance was proxied by Return on Assets (ROA), while firm size, measured by the natural logarithm of total assets, served as a control variable. Panel data were analyzed using the Random Effect Model (REM) with EViews 13. The results indicate that environmental disclosure has a positive and significant effect on ROA (β = 13.295; p = 0.028), governance disclosure also positively affects ROA (β = 10.648; p = 0.046), whereas social disclosure has no significant effect (β = −6.526; p = 0.234). Simultaneously, ESG disclosure significantly influences financial performance (F = 10.553; p < 0.001), with an adjusted R² of 31.52%. This study contributes to the ESG literature by demonstrating that environmental and governance disclosures play a more substantial role than social disclosure in enhancing financial performance within Indonesia's mining sector, thereby strengthening the applicability of legitimacy and stakeholder theories in emerging markets.